2014
DOI: 10.1186/1746-6148-10-78
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne encephalitis virus (TBEV) – findings on cross reactivity and longevity of TBEV antibodies in animal sera

Abstract: BackgroundBy using animal sera as sentinels, natural TBEV foci could be identified and further analyses including investigations of ticks could be initiated. However, antibody response against TBEV-related flaviviruses might adversely affect the readout of such a monitoring. Therefore, the cross-reactivity of the applied TBEV serology test systems – enzyme linked immunosorbent assay (ELISA) and virus neutralization test (VNT) – as well as the longevity of TBEV antibody titres in sheep and goats were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
5
53
0
1
Order By: Relevance
“…However, we cannot rule out reinfection during this time period. This correlates with data reported from Klaus et al [49] where the persistence of TBEV antibodies could be demonstrated after 28 months. The present study was restricted to areas of pasturage where sheep and goats breed, which restricted the study area.…”
Section: Discussionsupporting
confidence: 93%
“…However, we cannot rule out reinfection during this time period. This correlates with data reported from Klaus et al [49] where the persistence of TBEV antibodies could be demonstrated after 28 months. The present study was restricted to areas of pasturage where sheep and goats breed, which restricted the study area.…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm that VNT performed in parallel with co‐circulating flaviviruses is more specific than the ELISA tests for WNV antibody detection, supporting the usefulness of this technique as confirmatory method. Furthermore, this study corroborates that cross‐reactions in serological diagnostic methods (including VNT) exist not only between flaviviruses within the same serocomplex (WNV and USUV), but also from different serocomplexes (WNV/USUV and BAGV), as previously observed with other flaviviruses such as Japanese encephalitis virus and tick‐borne encephalitis virus (Klaus, Ziegler, Kalthoff, Hoffmann, & Beer, ; Stiasny, Aberle, & Heinzl, ). These observations may also be relevant when it comes to human diagnosis in areas with co‐circulation of WNV and other flaviviruses such as yellow fever, Japanese encephalitis, zika, dengue or tick‐borne encephalitis viruses in travellers that have visited endemic countries and in people vaccinated against some of these viruses.…”
Section: Discussionsupporting
confidence: 88%
“…Possible previous infection with WNV is difficult to exclude as these horses had an unknown infection date and were not selected based on clinical symptoms. This may have resulted in more horses having lower TBEV antibody responses due to infections months or years in the past or a faster decline of TBEV antibodies post‐infection compared to WNV (Klaus et al., , ).…”
Section: Discussionmentioning
confidence: 99%